GWAS of follicular lymphoma reveals allelic heterogeneity at 6p21.32 and suggests shared genetic susceptibility with diffuse large B-cell lymphoma - Smedby K.E. (Public Library of Science, 2018)
10.1371/journal.pgen.1001378